2019
DOI: 10.1002/open.201900045
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Imaging for Cysteine Detection In Vivo with High Selectivity

Abstract: As an essential amino acid, cysteine is involved in various biosynthetic and metabolic processes, such as protein synthesis, hormone synthesis, and redox homeostatic maintenance. Inordinate cysteine levels are often associated with serious diseases. Thus, designing and synthesizing a novel fluorescent probe for determining the concentration of cellular cysteine, which could indirectly monitor the prevalence of these diseases, is essential. We developed a florescence probe P−Cy with good sensitivity for cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, it is important to consider that not all of the reported sensors provide the same degree of performance and some only possess small signal changes that may render them impractical for many applications. In addition, the quality of the reported data is also highly variable, with some sensor characterization data seeming to be of questionable quality [ 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. More specifically, in the course of preparing this review, we found that the data (such as the spectra, affinity titrations, or specificity tests) for some reported sensors did not appear to be internally consistent within a single publication.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to consider that not all of the reported sensors provide the same degree of performance and some only possess small signal changes that may render them impractical for many applications. In addition, the quality of the reported data is also highly variable, with some sensor characterization data seeming to be of questionable quality [ 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. More specifically, in the course of preparing this review, we found that the data (such as the spectra, affinity titrations, or specificity tests) for some reported sensors did not appear to be internally consistent within a single publication.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Many previously reported efforts have focused on the synthesis of dyes for cysteine detection, with at least 24 synthetic dye-based reported to function in detecting cysteine in the past five years (Table 2) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 ]. Of these, several can be targeted to the mitochondria [ 262 , 282 , 285 , 286 ], the Golgi apparatus [ 259 , 276 ], the endoplasmic reticulum [ 274 , 275 ] and the lysosome [ 277 ].…”
Section: Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are only 20 basic natural AAs, the combinations of these AAs in different ways make up a tremendous amount of proteins with abundant functions and each amino acid plays an individual characteristic role. For example, cysteine (Cys) is the only one containing the sulfhydryl group among the natural amino acids that may contribute to regulating redox homeostasis and maintaining the spatial structure of proteins [ 5 , 6 ]. Whether an excess or deficiency of Cys could cause some heavy diseases such as abnormal hematopoiesis, neurotoxicity, Alzheimer’s disease, retarded growth, edema, muscle/fat loss, hair depigmentation, skin lesions, liver damage and so on [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cysteine (Cys) is the only one containing the sulfhydryl group among the natural amino acids that may contribute to regulating redox homeostasis and maintaining the spatial structure of proteins [ 5 , 6 ]. Whether an excess or deficiency of Cys could cause some heavy diseases such as abnormal hematopoiesis, neurotoxicity, Alzheimer’s disease, retarded growth, edema, muscle/fat loss, hair depigmentation, skin lesions, liver damage and so on [ 6 , 7 , 8 ]. Lysine (Lys) is a kind of important essential amino acid that cannot be manufactured by the body itself and, thus, must be taken in through daily diet.…”
Section: Introductionmentioning
confidence: 99%